PENDEKATAN PEDAGOGIS INKLUSIF UNTUK MINORITAS - Winsidi; Solehan; adminptjk adminptjk (CV JK Riset Publishing Group, 2025)
Inclusive pedagogical approaches for minorities represent a transformative strategy in education aimed at empowering marginalized groups. This research explores a comprehensive approach integrating flexible curriculum, responsive teaching methodologies, and digital technology to create inclusive learning environments. The study highlights the importance of reconstructing educational systems that respect individual uniqueness, accommodate cultural diversity, and develop teacher competencies in facilitating cross-cultural learning. Digital technology and innovative pedagogical methods serve as accelerators in creating equitable dialogue spaces. The conclusion emphasizes that inclusive education is a strategic investment in building a just society, producing empathetic generations capable of navigating global diversity